Peran Pemerintah Desa Terhadap Kegiatan Ekonomi Masyarakat Dusun Nebura Desa Koja Gete - Irfan, Ali; Abdul Kholik; Muhamad Taufik Arifin (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to determine the role of the Village Government towards the Economic Activities of the Nebura Hamlet Community of Koja Gete Village. Qualitative research can show research on community life, history, behavior, or kinship relationships. This research took place in Nebura hamlet, Koja Gete village, East Alok sub-district, Sikka district, East Nusa Tenggara (NTT) province. This research was conducted in February 10, 2023 - March 10, 2023. The technique of collecting data uses observation, interviews and documentation. Data analysis can be interpreted as an activity of discussing and understanding data in order to find meaning, interpretation and certain conclusions from all data in the research. In Koja Gete Village, the government's attention has not been maximized for the community. The government has not prepared equipment and supplies for farming activities. For example: mills, tractors, and so on. Many problems are faced by the community in agricultural activities, especially problems with pests in plants, waterways, and also the income of farm laborers who do not meet their daily needs so they look for other alternatives to meet their needs.